CHANGE OF REFLECTIVE CHARACTERISTICS OF ANISOTROPIC ENVIRONMENTS AT VARIATIONS OF PARAMETERS OF THE FILLER: circular POLARIZATION - D. V. Gololobov; E. Yu. Ivanova; V. B. Kirilchuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of the frequency dependencies the reflection coefficient of the modules of electromagnetic wave with orthogonal polarizations in a circular basis of electrodynamics parameters of anisotropic environment from plasma like type filler are given. The laws of frequency characteristics transformation of the waves with circular polarization at fixed electrodynamics parameters of stream of particles that penetrate a magnet the dielectric filler. The results obtained can be used as reference information about the reaction environment of the radio search and identification system of anisotropic not uniformity against the isotropic spreading environment.